(untitled) (Homoeopathy for All, 2025)
Nausea can stem from a variety of causes. Some people are highly sensitive to motion or to certain foods, medications, or the effects of certain medical conditions. All these things can cause nausea and vomiting Nausea is stomach discomfort and the sensation of wanting to vomit. It can be a precursor to vomiting the contents of the stomach. Motion sickness is a common cause of nausea and vomiting and so is morning sickness during pregnancy.